2021
DOI: 10.21037/qims-20-1013
|View full text |Cite|
|
Sign up to set email alerts
|

Computed tomography-based opportunistic osteoporosis assessment: a comparison of two software applications for lumbar vertebral volumetric bone mineral density measurements

Abstract: Background: We aimed to compare two volumetric bone mineral density (vBMD) analysis programs, regarding (I) agreement of vBMD values based on mono-and dual-energy computed tomography (MECT and DECT) scans and (II) suitability for analyzing DECT data obtained at different energies. Methods:We retrospectively analyzed two abdominal CT datasets: one performed in a MECT scan (vertebrae L1-L3) and one in a DECT scan (vertebrae L1-L4). Each dataset included different individuals [MECT 15 patients (45 vertebrae) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…However, we could not obtain satisfactory results utilizing DXA while treating patients with degenerative diseases, which was confirmed by many previous studies. 13 , 14 , 32 , 33 Quantitative CT (QCT) was introduced as a reliable method of assessing the bone quality with trabecular BMD instead of areal BMD measured by DXA. 34 However, it cannot be performed routinely in most hospitals due to patients’ unwillingness to undergo additional examinations.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not obtain satisfactory results utilizing DXA while treating patients with degenerative diseases, which was confirmed by many previous studies. 13 , 14 , 32 , 33 Quantitative CT (QCT) was introduced as a reliable method of assessing the bone quality with trabecular BMD instead of areal BMD measured by DXA. 34 However, it cannot be performed routinely in most hospitals due to patients’ unwillingness to undergo additional examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect when considering vBMD measurement is to be aware of the kVp used in the CT examination. A lower kVp yields exponentially higher HU values [ 29 , 30 ], and furthermore impact of kVp varies between different tissues [ 28 , 29 ]. For this reason, vBMD analysis with software methods based on internal tissue references, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For the vBMD analysis, Mindways qCT PRO software, version 2 (Mindways, Austin, TX, USA) was used as described in detail earlier [ 28 ]. In brief, preceding the study, calibration scans with Mindways dedicated phantom were performed, repeated monthly during the study period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have shown that abdominal and spinal bone marrow adipose content influences the QCT measurements of vertebral BMD (8)(9)(10)(11)(12)(13). Dual-energy computed tomography (DECT) employs a high-and low-energy switching scanning method with a material decomposition (MD) technique that also allows the accurate measurement of vertebral BMD, which has shown preliminary advantages (14)(15)(16)(17). However, it is possible that the DECT measurements of BMD were influenced, to some extent, by abdominal adipose content.…”
Section: Introductionmentioning
confidence: 99%